Effect of Working Capital and Leverage on Profitability (Study on Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange 2014 - 2018 Period) - Irdawati Irdawati; Abdul Rakhman Laba; Muhammad Yunus Amar (LAFADZ JAYA Publisher, 2022)
This study aims to testThe Effect of Working Capital and Leverage on Profitability (Study of Manufacturing Companies in the Food and Beverage Sub-Sector Listed on the Indonesia Stock Exchange for the Period 2014 - 2018). The population in this study were all food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2014-2018 period. TtechniqueSampling in this study using purposive sampling. Based on the predetermined criteria, the researchers determined 14 food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange. The data were processed using SPSS version 25. The results show that Days of Inventory Outstanding (DIO), Days of Sale Outstanding (DSO), Days of Payable Outstanding (DPO) and DER have a simultaneous effect. On Profitability, shows that DIO, DSO, DPO and DER together are able to increase profitability, DIO has an effect on profitability, DSO has a negative effect on profitability. DPO has no effect on profitability.